VHF Crystal Oscillator for Satellite Receiver - Olesco, Richard O. (Philippine Engineering Journal; Vol 17 No 1 (1996), 2021)
This paper will discuss the design of a crystal oscillator used as a local oscillation (LO) for satellite receivers in the VHF band.